COURAGE IN HARPER LEE’S NOVEL TO KILL A MOCKINGBIRD - Baba, Maria C; Wanggai, Febe F I; Doi, Maksimilianus (Lantern: Journal of Language and Literature, 2022)
Creswell, J. (2014). Research design: qualitative, quantitative and mixed methods approaches. Los Angeles: University of Nebraska-Lincoln. Elmes. G. (2012). Research methods in psychology. Canada: Nelson Education. Klarer, M. (2013). An introduction to literary studies. New York: Routledge. Larrson, L. & Woolf, V. (2017). Walking Virginia Woolf’s London: An investigation in literary geography. London: Palgrave Macmillan. Mays, K. J. (2015). The Norton introduction to literature. New York: W. W. Norton & Co. Putman, D. (2010). The psychology of courage: modern research on an ancient virtue. Washington, DC: American Psychological Association. Turco, L. (2020). The book of literary terms: the genres of fiction, drama, nonfiction, literary criticism, and scholarship. Albuquerque: University of New Mexico Press.